Effect of producer gas staged combustion on the performance and emissions of a single shaft micro-gas turbine running in a dual fuel mode - Sadig, H. (Elsevier B.V., 2017)
Producer gas from biomass gasification has a potential to cover a considerable part of power production in the future, the availability and variety of biomass put it as the fourth energy resource. The use of producer gas fuels in gas turbine engines can help mitigating problems related to fossil fuels depletion, emissions and biomass waste disposal. In this work, the effect of the staged combustion of a simulated low calorific value producer gas fuels on the performance and emissions of a single shaft micro gas turbine was investigated experimentally. In order to perform the experiments, the micro gas turbine system was characterized first with the liquefied petroleum gas (LPG) and then tested with two producer gas fuels, producer gas1 (10.53 H2, 24.94 CO, 2.03 CH4, 12.80 CO2, and 49.70 N2) and producer gas2 (21.62 H2, 32.48 CO, 3.72 CH4, 19.69 CO2, and 22.49 N2) in a dual fuel mode. Two injection methods were proposed and tested for producer gases including radially and axially injection. The tests were examined in terms of LPG fuel replacement, turbine entrance temperature, combustor efficiency, turbine efficiency, and emission characteristics at different LPG fuel replacement ratios. The study showed stable operation with a maximum LPG replacement of 42 and 56 for the radially injected producer gas1 and producer gas2, respectively. While for the axially injected producer gas fuels, the maximum achieved LPG replacement ratio was 38 and 52 for producer gas1 and producer gas2, respectively. A relatively higher efficiencies for the combustor and turbine with a remarkable reduction in NOx emissions were achieved when LPG fuel was replaced with producer gas fuels. On the other hand CO emissions were increased for both injection methods. © 2015 Energy Institute